Urban Drainage System Review Based on Regional Spatial Planning in Madiun City Area - Wiwin Wulandari; Sri Sunarjono; Purwanti Sri Pudyastuti (Eduvest - Journal of Universal Studies, 2025)
This study evaluates the urban drainage system in the Madiun City area through the lens of regional spatial planning. It highlights the impacts of land-use changes on drainage congestion and flooding, emphasizing the need for sustainable spatial policies. The research identifies key factors contributing to drainage issues, such as the closure of primary waterways and inadequate maintenance. Utilizing a combination of qualitative and quantitative analysis, the study assesses hydrological conditions and the effectiveness of proposed eco-drainage solutions, including infiltration wells and retention ponds. The findings underscore the importance of integrating drainage management with spatial planning to mitigate flood risks, especially in the context of climate change.